Daya Rusak Spodoptera frugiperda J. E. Smith pada Tanaman Jagung yang Diberi Perlakuan Pestisida Nabati Daun Pepaya dan Bawang Putih - Hartini Hartini; Muhammad Indar Pramudi; Samharinto Soedijo (www.ulm.ac.id, 2022)
Plant Pest Organisms (PPO) that have recently become a problem in corn cultivation are Fall Armyworm (FAW) or the armyworm Spodoptera frugiperda J. E. Smith. The damage of S. frugiperda on sweet corn and feed is thought to be different and is not yet known. This study aims to determine the level of destruction of S. frugiperda on sweet corn and feed with control treatment of biological pesticides on papaya leaves and garlic, 30 ml/l water, 40 ml/l water, and 50 ml/l water. This study used a completely Randomized Design (CRD) with two factors. Corn varieties and concentrations of vegetable pesticides. The treatments used in this study were water control, chemical control, and three treatments of biological pesticide concentration with four replications. The results of observations 1-3 (age 0-2 weeks after planting/ WAP) have not found an attack, occurred on the study to 4-7 (age 3-6 WAP). Pesticides of papaya leaf and garlic affected the destructive power of S. frugiperda, where the concentration factor on the incidence of attack and attack intensity had a very significant effect, an interval of the variety factor had to make a difference on the incidence of attack but did not significantly affect the potency of the attack. The 50 ml/l concentration treatment on sweet corn and feed varieties was the best in suppressing the percentage of attack (12.50; 23.40%), attack intensity (5.92; 8.00%), and damage to the cob (1.79); 4.79%).